Applying Timor Leste Traditional Conflict Resolution on the Tigray War Conflict: Jaarsummaa and Qaalluu Method - Muhammad Abiel Dewa Pratama (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2023)
The Tigray War is an ongoing civil conflict that started on November 3, 2020, in Ethiopia's Tigray Region. The idea was first up in June 2005 by the International Criminal Court (ICC), which said that